Latinx teacher advocates engaged in social justice agendas: a LatCrit perspective - Espinoza, Pedro (Kansas State University, 2020)
Working with Culturally and Linguistically Diverse (CLD) students has been a challenge for many years. Classroom teachers and certified English as a Second Language (ESL) teachers struggle staying current with the pedagogical approaches and strategies to work with this student population. In order to help CLD students succeed in the classroom, teachers may implement effective teaching strategies. Additionally, teaching without knowing the students’ background knowledge can be problematic to all students. This study explored (a) how teachers who graduated from a federally funded bilingual and bicultural education program engage in justice agendas for their CLD students (b) the things these in-service teachers attribute as barriers and support systems in their social justice work (c) the educational strategies the in-service Latinx teachers value in their role as advocates in their social justice work. In order to examine the participants’ experiences regarding social justice, I used Qualitative and Critical Qualitative Research (CQR) as my overarching framework. Additionally, I used Critical Race Theory (CRT), but more specifically Latino/a Critical Race Theory (LatCrit) as my theoretical framework and trenzas y mestizaje (braids and mixture) as my methodological framework. My methodology was based on testimonios collected through the methods of individual pláticas and group pláticas (formal and/or informal conversations) elicited by the use of tesoros (treasures). Through CQR, my data was viewed through the lens of Trenzas y Mestizaje and LatCrit. These methodological and theoretical frameworks resulted in analysis of my data through braiding the participants’ experiences and/or testiminios. By combing through data of the transcribed testimonios collected from the pláticas, I identified and braided the following prominent emerging themes: (a) Tesoros from students and families, (b) Relationships, (c) Advocacy for CLD students: High expectations of all students, (d) Barriers as pre-service and in-service teachers: Resilience, (e) Support system as pre-service and in-service teachers: hechale ganas/work hard, (f) Effective classroom strategies, (g) Importance of parent and family involvement. Each of these themes is presented and analyzed. All seven emerging themes help to illustrate the types of barriers the participants encountered during the process of becoming teachers and during their professional careers. These themes illustrate the type of support the participants currently receive and have received from their colleagues and administrators. Additionally, these themes depict the type of support the participants provide for their CLD students and families and explain different ways the participants personally relate to their students. Individually, all the themes are outlined and discussed. Additionally, the following recommendations for future research are also discussed: (1) More quantitative and mixed methods studies are recommended, (2) Implementation of classroom observations, (3) Selection of participants from different linguistic and cultural backgrounds, (4) Provide more federal funding for pre-service and in-service programs to support current and future teachers of color. Furthermore, the following three recommendations for practice are also addressed: (1) Recruitment and retention initiatives for teachers of color, (2) Provide opportunities for growth and professional development for teachers working with Culturally and Linguistically Diverse Students (CLDs), (3) Identify significant online educational strategies to implement with CLDs.
Keywords: Latinx teacher advocates; Trenzas y mestizaje; LatCrit